Implementasi Customer Relationship Management (CRM) di Atria Hotel Malang - Wicaksono, Didit Rahadi (Jurnal Kajian dan Terapan Pariwisata, 2021)
Atria Hotel Malang is one of the four-star hotels located in Malang City which is in the heart of Malang city. The hotel management needs to implement a marketing strategy in the form of Customer Relationship Management (CRM) to create customer satisfaction with the services provided. In implementing the CRM strategy, there are four implementations to create and manage customer relationships, namely: (1) Identification; (2) Differentiation; (3) Interaction; (4) Customize. The research method used by the researcher is a qualitative research method. Based on the results of the study, it can be concluded that the implementation of Customer Relationship Management (CRM) in the sales and marketing department in maintaining and maintaining good relationships with customers has been carried out well in developing brand awareness to the public, but in the application of customer relationship management it has not been carried out effectively because it is still there are many customer databases in the corporate segment that accumulate and are no longer valid as a result of uneven relationship management to customers. Atria Hotel Malang requires creative and innovative ideas every year to be able to improve product quality and company image in front of consumers.